Relationships Between Neuronal Oscillatory Amplitude and Dynamic Functional Connectivity. (16th May 2018) - Tewarie, Prejaas; Hunt, Benjamin A E; O'Neill, George C; Byrne, Aine; Aquino, Kevin; Bauer, Markus; Mullinger, Karen J; Coombes, Stephen; Brookes, Matthew J
Abstract: Event-related fluctuations of neural oscillatory amplitude are reported widely in the context of cognitive processing and are typically interpreted as a marker of brain "activity". However, the precise nature of these effects remains unclear; in particular, whether such fluctuations reflect local dynamics, integration between regions, or both, is unknown. Here, using magnetoencephalography, we show that movement induced oscillatory modulation is associated with transient connectivity between sensorimotor regions. Further, in resting-state data, we demonstrate a significant association between oscillatory modulation and dynamic connectivity. A confound with such empirical measurements is that increased amplitude necessarily means increased signal-to-noise ratio (SNR): this means that the question of whether amplitude and connectivity are genuinely coupled, or whether increased connectivity is observed purely due to increased SNR is unanswered. Here, we counter this problem by analogy with computational models which show that, in the presence of global network coupling and local multistability, the link between oscillatory modulation and long-range connectivity is a natural consequence of neural networks. Our results provide evidence for the notion that connectivity is mediated by neural oscillations, and suggest that time–frequency spectrograms are not merely a description of local synchrony but also reflect fluctuations in long-range connectivity.